Crack initiation and propagation in molded gypsum specimens with pre-cracked single flaws - Chong, Wanling. (2012)
This paper summarises the results of an investigation on the influence of flaw inclination on crack initiation and propagation for molded gypsum specimens under compression. Molded gypsum specimens with 1.3mm wide flaws of inclinations 75°, 80°, 85° and 90° were tested. Uniaxial compression was conducted using two INSTRON Uniaxial Compression Machines and the entire process was filmed by a SONY HDR-XR150 digital camcorder and a PHANTOM v310 high speed camera. Cracking initiation and propagation sequences were analysed using high speed